Tecnologia e inovação na produção de whey protein e pre-workout no Brasil - Kawano, Gabriel Yamamoto (Universidade Federal de São Carlos, 2024)
The notion that nutrition can play a crucial role in promoting a healthy life is not new. As early as antiquity, Hippocrates correlated food with medicine. In recent years, the growing interest in a healthy lifestyle has driven the demand for dietary supplements. These products have been marketed for various purposes, such as increasing muscle mass and reducing body fat. This study aimed, through a literature review conducted from January to October 2024, by researching descriptors across different databases, to understand the technologies and innovations involved in the production of dietary supplements in Brazil, with a focus on the processing of whey protein and pre-workout products. It was found that the literature addresses more aspects related to whey protein than to pre-workout supplements. Furthermore, the market offers a variety of whey protein-based products, such as protein bars and yogurts, and caffeine-based products, such as super coffee. Additionally, few sources discussed the use of dietary supplements as essential ingredients for the development of new food products. Notably, for pre-workout supplements, no innovations were identified among the studies analyzed. It is concluded that dietary supplements show high potential for the development of new products, offering health benefits and enhanced performance. Moreover, the need for further studies on the new potential uses of these products as food ingredients was identified.
Technology and innovation in the production of whey protein and pre-workout in Brazil
Keywords: Suplementos alimentares; Concentrado proteico; Atividade física; Potencialidades; Food supplements; Protein concentrate; Physical activity; Potentialities; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS